Stone elephant, Dr. Bhau Daji Lad Museum - Ghosh, Ayan (2023)
The original elephant, after which Elephanta Island was named by the Portuguese, is displayed outside Dr. Bhau Daji Lad Museum. The statue was originally at Rajabunder jetty on the south shore of Elephanta Island, formerly referred to as Gharapuri. In 1987, UNESCO declared Elephanta Island a World Heritage Site for its collection of Hindu cave temples.